Comparative Models of Social Responsibility - Adizes, Ichak; Weston, J. Fred (Academy of Management Journal, 1973)
The polar classical capitalist and communist models of achieving the public interest are being changed and further modifications have been advocated. However, weaknesses common to the proposed changes stem from their closed system, segmented approach. Five salient developments are summarized, indicating their significance and the derived parameters required as elements of a new solution model.